2014
DOI: 10.5125/jkaoms.2014.40.5.225
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bony changes and tooth displacement in the mandibular cystic lesion involving the impacted third molar

Abstract: ObjectivesThe purpose of this retrospective study is to find the differentiating characteristics of cystic and cystic-appearing lesions that involve the impacted mandibular third molar by analyzing panoramic radiographs and computed tomography images, and to aid the preoperative diagnosis.Materials and MethodsEighty-one patients who had a mandibular cystic or cystic-appearing lesion that involved impacted mandibular third molar and underwent cyst enucleation were included in the study. The preoperative panoram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…However, in this study, more than half of OKCs presented bony expansion particularly at the posterior maxilla and ramus of the mandible and this is in consistent with a previous study [8]. In a study [11], OKC caused more displacement of impacted third molar in mesio-distal compared to ameloblastoma and DC. In this study, 30% of OKCs found to cause tooth displacement.…”
Section: Multiple Lessions Associated With Nevoid Basal Cell Carcinomsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in this study, more than half of OKCs presented bony expansion particularly at the posterior maxilla and ramus of the mandible and this is in consistent with a previous study [8]. In a study [11], OKC caused more displacement of impacted third molar in mesio-distal compared to ameloblastoma and DC. In this study, 30% of OKCs found to cause tooth displacement.…”
Section: Multiple Lessions Associated With Nevoid Basal Cell Carcinomsupporting
confidence: 92%
“…In this study, the age ranged from 10 to 87 years old similar to previous report [6]. The mean age recorded in our population was 31.5 years old, in consistent with previous studies [8,11]. The highest frequency of cases affected patients in the second and third decades in agreement with existing researches [7,12].…”
Section: Multiple Lessions Associated With Nevoid Basal Cell Carcinomsupporting
confidence: 92%
“…Dentigerous cysts are associated with unerupted tooth/teeth. Their presence may prevent associated teeth from eruption and their displacement in the jaw . Benn and Altini suggested that dentigerous cysts in paediatric population are of inflammatory origin while in mature teeth they are developmental in origin.…”
Section: Discussionmentioning
confidence: 99%
“…Enucleation of the dentigerous cyst & extraction of the associated permanent tooth/remove the pathological tissues and has shorter treatment period, but may lead to functional & aesthetic as well as possible psychological trauma to the child that result from tooth/teeth loss and necessitate extensive treatment later.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO histological classification of odontogenic tumours, about one-half of KCOTs originate at the angle of the mandible and more than 90% of UAs involve the mandibular posterior region. These cystic lesions are often associated with impacted mandibular third molars, some reports indicated that up to 80% of these lesions are associated with an unerupted mandibular third molar ( 2 , 3 ). The standard treatment for those lesions is enucleation and extraction of the involved teeth, but the treatment plan was difficult to work out for the huge cystic lesions with deeply impacted teeth.…”
Section: Introductionmentioning
confidence: 99%